2009
DOI: 10.1016/j.tube.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis ethambutol resistance: Concordance between phenotypic and genotypic test results

Abstract: s u m m a r y embB306 mutations are potential markers for detecting ethambutol resistance in clinical Mycobacterium tuberculosis isolates. However, more recently, embB306 mutations have been found in ethambutol susceptible isolates and an association with broad drug resistance rather than ethambutol resistance has been reported.To further investigate this question, we analyzed the association between embB306 mutations and phenotypic ethambutol resistance among 197 isolates from a drug resistance survey perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 20 publications
(26 reference statements)
1
25
2
Order By: Relevance
“…In comparison with phenotypic DST, the MTBDRsl showed low specificity and sensitivity (55%), mainly due to embB mutations MIC values resolved the discrepancies between LiPA and DST but raised concerns on phenotypic EMB DST by MGIT. Our results support the findings of PLINKE et al [25] reporting that strains, phenotypically susceptible to EMB and carrying mutations at codon 306 of the embB gene, were found resistant after retesting. These findings raise concerns regarding the standardisation of phenotypic DST for EMB.…”
Section: Embsupporting
confidence: 92%
“…In comparison with phenotypic DST, the MTBDRsl showed low specificity and sensitivity (55%), mainly due to embB mutations MIC values resolved the discrepancies between LiPA and DST but raised concerns on phenotypic EMB DST by MGIT. Our results support the findings of PLINKE et al [25] reporting that strains, phenotypically susceptible to EMB and carrying mutations at codon 306 of the embB gene, were found resistant after retesting. These findings raise concerns regarding the standardisation of phenotypic DST for EMB.…”
Section: Embsupporting
confidence: 92%
“…Because conventional culturebased phenotypic methods of EMB susceptibility testing are notoriously problematic, the presumably inaccurate conventional drug susceptibility results may be the major cause of the "EMBsusceptible" isolates that harbored embB mutations (13,14). Similarly, the problems of conventional proportion susceptibility were most likely responsible for the discrepancies between molecular and phenotypic EMB resistance test results (15). Here, our results demonstrate that ethambutol resistance determined by the broth microdilution MIC method revealed better correlation with embB mutations in MDR-TB isolates.…”
mentioning
confidence: 66%
“…Although the association between embB306 mutation and EMB resistance has been identified, the exact role of embB306 mutations in the development of ethambutol resistance and multidrug resistance in M. tuberculosis is not fully understood. Since the majority of EMB resistance occurs in MDR strains of M. tuberculosis, it is likely that embB306 substitutions were not directly associated with ethambutol resistance but rather with MDR-TB, and it is concluded that embB306 mutations can serve as a marker for development of drug resistance [20,21].…”
Section: Discussionmentioning
confidence: 99%